Aerosol - cloud interactions in the Arctic boundary layer, Ny - Ålesund, Svalbard - Ryberg, Karin (2006)
Aerosols take part in the cloud formation process by acting as cloud condensation nuclei. An increase in anthropogenic aerosols in the atmosphere is believed to have significant effects on cloud properties and therefore weather and climate. In this study, aerosol – cloud interactions in the Arctic boundary layer are investigated, by using data from years 2003 and 2004, observed at Ny-Ålesund, Svalbard. In-situ measurements of aerosol particle size distributions from the Zeppelin station, 474m asl, are compared with lidar measurements of cloud and aerosol backscatter from Ny-Ålesund by statistical methods. From the lidar backscatter data three variables were educed: average backscatter from the boundary layer (0 - 2km), backscatter from 474m altitude and backscatter from 948m altitude. With data from the first variable a clear relationship between particle size and average backscatter can be seen, showing positive correlation for small aerosols, whereas negative correlation is observed for large aerosols (>100nm diameter) during times of high backscatter. The other two variables made it possible to study the aerosol – cloud interaction during periods when the station was in cloud free air whereas the level just above it was within clouds. This is an analogue to aircraft measurements where measurements are first made below clouds and then inside clouds. The result gave a rather complex picture, however the interpretation is that this complexity is due to a much stronger influence by the clouds on the aerosol properties than vice versa. Validerat; 20101217 (root)